2021
DOI: 10.1109/tse.2019.2938525
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Good Work Habits in Software Developers through Reflective Goal-Setting

Abstract: Software developers are generally interested in developing better habits to increase their workplace productivity and well-being, but have difficulties identifying concrete goals and actionable strategies to do so. In several areas of life, such as the physical activity and health domain, self-reflection has been shown to be successful at increasing people's awareness about a problematic behavior, motivating them to define a self-improvement goal, and fostering goal-achievement. We therefore designed a reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 75 publications
(134 reference statements)
0
12
0
Order By: Relevance
“…The problem of vague goals and personal success metrics described by our interviewees has also appeared in prior work [68,70]. Providing tools for determining the criteria for success can provide learners with contextual awareness beyond their immediate task needs, and subsequently prompt them to diversify their support systems for learning ML.…”
Section: Personalized Success Metrics For Gauging Learning Progressmentioning
confidence: 75%
See 1 more Smart Citation
“…The problem of vague goals and personal success metrics described by our interviewees has also appeared in prior work [68,70]. Providing tools for determining the criteria for success can provide learners with contextual awareness beyond their immediate task needs, and subsequently prompt them to diversify their support systems for learning ML.…”
Section: Personalized Success Metrics For Gauging Learning Progressmentioning
confidence: 75%
“…An adaptive learning process can lead to the discovery of unforeseen problems and accelerate problem resolution towards learner's objectives. Continual re-evaluation and iteration of the goals [68] could serve as invaluable feedback of the learning progress (Fig. 1 Stage 3).…”
Section: Personalized Success Metrics For Gauging Learning Progressmentioning
confidence: 99%
“…Regarding the field of software development in particular, future work should engage with the literature on engineer productivity to design effective gamification [73]. For instance, the lessons of recent work on goal-setting methods to foster good habits among software developers could be applied to this question [74].…”
Section: B Future Workmentioning
confidence: 99%
“…Evidence suggests that interventions that encourage more planning at work have beneficial effects on productivity [26]. Research groups are experimenting with different prototypes to facilitate work planning, such as conversational agents to help knowledge workers plan daily [27], or interventions to facilitate reflection and goal-setting [28]. Those recent studies have shown promising results about the beneficial impact of encouraging more planning through prototypes of smart assistants and short-term interventions.…”
Section: Effectiveness Of Individual Planning Tools and Strategiesmentioning
confidence: 99%